ChemInform Abstract: A Ligand‐Free Palladium‐Catalyzed Cross‐Coupling of Aryl Sulfinates with Aryl Bromides. Issue 49 (3rd December 2013) - Ortgies, Dirk H.; Forgione, Pat
Abstract A ligand free Pd‐catalyzed process is presented to allow the synthesis of biphenyls by desulfinylative cross‐coupling of aryl sulfinates with aryl bromides.